Progressive tax reforms in flat tax countries - Salvador Barrios Cobos; Viginta Ivaskaite-Tamosiune; Anamaria Maftei; Edlira Narazani; Janos Varga (University of Essex, Institute for Social and Economic Research (ISER), 2019)
Much of the literature on flat tax reforms has highlighted the benefits of introducing flat personal income tax systems in transition economies. The advocated benefits of flat tax systems range from their simplicity, higher compliance and lower distortionary effects on growth and employment. These arguments have often been cited to support policy recommendations favouring the adoption of flat tax systems in Central and Eastern European (CEE) countries in the 1990s and the 2000s. However since income inequality is notoriously high in these countries, the question of introducing some progressivity in the tax system has come to the fore in both policy and academic circles. In this paper, we analyse the fiscal, redistributive and macroeconomic impact of (re-)introducing progressivity in a number of CEE countries with flat tax systems. Combining microsimulation and macro models, we find that a significant reduction in income inequality can be achieved by moving from a flat to a progressive tax system with positive, albeit negligible, macroeconomic and employment impact. The magnitude of these effects depends on country-specificities and tax system characteristics, due in particular to the existence of tax allowances and tax credits.
Keywords: D04; D31; D63; E62; H23; 330; Flat tax; microsimulation model; DSGE model; inequality progressivity; employment; growth